A scoping review of emotional contagion research with human subjects: identifying common trends of previous research and potential areas for future research - Michalec, Barret; Forbes, Chad E.; Pardon, Kevin; Ayala, Bella; Beltran, Diego Guevara; Douille, Clarice; Felix, Kaitlyn; Gnall, Samantha; Hoenack, Michael; McKeever, Brooke; Nguyen, Daniel; Piemonte, Nicole; et al. (Frontiers in Psychology, 2025)
IntroductionEmotional contagion (EC) involves the automatic mimicry and synchronization of expressions, vocalizations, and movements, resulting in emotional alignment between individuals. Despite consistent scholastic explorations of the various nuances and tenets associated with emotional contagion processes and outcomes, there has yet to be a thorough review of human subjects-based emotional contagion research.MethodsThis review examines human subjects EC research trends, analyzing 277 articles (published from 1992 to 2022) to identify common conceptualizations, triggers, and measurement methods.ResultsAnalyses indicated that Hatfield et al.’s classic conceptualization is the most cited, and common triggers include facial expressions in images and videos, and real-time interactions - though many studies did not stimulate EC. While many studies did utilize validated EC scales, about 28% of the studies reviewed used non-validated questions to measure EC. Moreover, the EC research reviewed heavily relies on college-aged, predominantly white participants, indicating a need for more diverse samples.DiscussionFuture EC research should explore processes and nuances associated with EC among older adults, minoritized groups, and diverse contexts (e.g., healthcare, schools), using novel triggers and multiple measurement methods.